ENGAGING IN CORPORATE SOCIAL RESPONSIBILITY PRACTICES BY COMMERCIAL BANKS IN CROSS RIVER STATE (NAU Journal of Technology and Vocational Education, 2024)
The study determined how commercial banks in Cross River State are engaging inethical marketing practices and community involvement practices all aspects ofcorporate social responsibility practices. Two research questions guided the study andtwo null hypotheses were tested at 0.05 level of significance. Survey research designwas adopted for the study. Population for the study comprised 578 communityrepresentatives in Cross River State. A sample size of 216 was drawn using multi-stagesampling technique. For effective investigation a 24 item structured, validatedquestionnaire was used for collection of data from the respondents. The reliability of theinstrument was established using split half method and a reliability co-efficient of 0.82was obtained. Data collected were analyzed using mean scores for the researchquestions. The hypotheses were tested using One-way analysis of variance. Thefindings of the study revealed among others that the commercial banks in Cross RiverState poorly engage in corporate social responsibility practices. It was recommendedamong others that commercial bank owners should organize in-house ethical training tohelp their employees make appropriate ethical decisions to meet the ethical concerns oftheir consumers and the host community.